Dynamics of the Working-Class Authoritarianism and Power Relations in the GIG Economy Indonesia - Allen Pranata Putra (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2026)
This study examines the dynamics of working-class authoritarianism and power relations in Indonesia’s gig economy, with a focus on online transportation workers. The research addresses the paradox of why workers positioned in vulnerable and exploitative labor structures often accept platform domination and resist collective opposition. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and documentation involving nine informants from government and private-sector backgrounds. The findings show that the relationship between digital platforms and workers is structurally asymmetrical, despite being framed as an equal partnership. Platforms exercise control through algorithms, incentives, ratings, and sanctions, while workers remain economically dependent on the system. The study also finds that ideological hegemony operates through narratives of flexibility, independence, and digital entrepreneurship, which normalize inequality and weaken critical class consciousness. In this context, working-class authoritarianism emerges as a psychosocial response to economic insecurity and the need for stability. The study concludes that domination in the gig economy is sustained not only through technological and economic control, but also through the production of consent. These findings highlight the need for stronger labor protection and the development of workers’ critical awareness in the digital economy.